The Viterinary Profession in Greece: Review of the present and prospects for the future. IV Anticipated developments for veterinary science.. A. Expectations of the profession - ΧΑΤΖΗΟΛΟΣ, ΒΑΣΙΛΕΙΟΣ Κ. (Journal of the Hellenic Veterinary Medical Society, 2019)
Although the future role of Vererinary Science in society is definitely seen as a very important one, success depends primarily on the veterinarian's desire to adapt to new situations, meet challenges created by the scientific revolution, and accept his many difficult professional responsibilities. For a better understanding of what is entailed, discussion is made of (1) the role of the veterinarian in the task of increasing animal protein supply by developing more productive but less demanding farm animals; (2) the basic nutritive elements and food requirements for man and animal; (3) some of the latest scientific developments related to animal science; (4) the importance of extensive veterinary participation in the development of scientifically desired features of farm animals — a participation thus far either not fully realized or prohibited by law; (5) the search for new sources of animal feed, such as residue from the breakdown of cellulose; and (6) the changes needed in the veterinary profession, including establishment of another Veterinary School and an Institute of Veterinary Science in order to meet the new social, economic, and environmental demands.